Dual-stimuli-responsive polymer-coated mesoporous silica nanoparticles used for controlled drug delivery - Yang, Mei-Yan; Tan, Lei; Wu, Hai-Xia; Liu, Chuan-Jun; Zhuo, Ren-Xi (Journal of applied polymer science, 2015)
ABSTRACT In this article, a temperature‐ and pH‐responsive delivery system based on block‐copolymer‐capped mesoporous silica nanoparticles (MSNs) is presented. A poly[2‐(diethylamino)ethyl methacrylate)] (PDEAEMA)‐b‐poly(N‐isopropyl acrylamide) (PNIPAM) shell on MSNs was obtained through the surface‐initiated atom transfer radical polymerization. The block copolymer PDEAEMA‐b‐PNIPAM showed both temperature‐ and pH‐responsive properties. The release of the loaded model molecules from PDEAEMA‐b‐PNIPAM‐coated MSNs could be controlled by changes in the temperature or pH value of the medium. The as‐desired drug‐delivery carrier may be applied to biological systems in the future. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42395.